Un’architettura di segni. Il pensiero di Merleau-Ponty tra fenomenologia ed ermeneutica - Ghilardi, Marcello (Scenari, 2024)
This essay wants to show how Merleau-Ponty opens a middle path, which may appear both phenomenological and hermeneutic, between the two extremes of a vision that encompasses all otherness and prevents all development by crystallizing the figures of knowledge and the world, on the one hand, and a thought that avoids questioning the transcendence and the overflow of phenomena, thus reducing itself to silence, on the other. In his writings and in the transcripts of the courses, we witness the awareness of the dialectical dynamics between world and language, self and other, map and territory, which emerge in the very formulation of a question – or from the very fact that a question must be formulated. The world of perception is both the world in which perception occurs and the world that perception is made up of. The slightest rational questioning about one’s own perception implies an “architecture of signs”, a complex system of words, concepts, forms of writing, gestures, dialogic or interpretative acts that are part of the world and, together, cooperate in its practical and theoretical organization.